2022
DOI: 10.3390/jcm11030822
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Status of Serum Albumin and Cognitive Function: A Retrospective Cohort Study

Abstract: Previous studies have found an association between serum albumin levels and cognitive function. However, the results of this association are inconsistent, and the effect of Apolipoprotein E (APOE) on the association is less clear. Using retrospective cohort data (2008–2020), we investigated whether chronic serum albumin was associated with cognitive performance in older adults. We further assessed how the APOE genotype modifies its relevance. A total of 2396 Korean veterans and their families who were aged 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Our results indicated that participants with a higher albumin level had a lower risk of cognitive impairment. Lower albumin levels have been reported to be correlated with poor cognitive performance in older adults [55][56][57]. In a previous study done in Japan [58], a positive association between the serum albumin/globulin ratio (A/G ratio) and cognitive function was found in 70-year-old and 80-year-old participants.…”
Section: Discussionmentioning
confidence: 92%
“…Our results indicated that participants with a higher albumin level had a lower risk of cognitive impairment. Lower albumin levels have been reported to be correlated with poor cognitive performance in older adults [55][56][57]. In a previous study done in Japan [58], a positive association between the serum albumin/globulin ratio (A/G ratio) and cognitive function was found in 70-year-old and 80-year-old participants.…”
Section: Discussionmentioning
confidence: 92%
“…However, regarding the relationship between nutritional risk and cognitive function, the intricate mechanisms underlying the effect of malnutrition on cognitive function have not been fully elucidated. Nevertheless, clinical evidence has shown many instances linking malnutrition to cognitive function [ 34 , 35 ]. Furthermore, malnutrition in patients with hip fractures results in a more pronounced decline in ADLs when combined with cognitive impairment [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Liver and Blood scores showed strong correlations, potentially reflecting the liver's blood filtration function and production of blood products. Both Liver and Blood were highly correlated with Brain, potentially reflecting known contributions of anemia and altered levels of liver products to brain aging [46][47][48][49] . Metabolic, Inflammation, and Kidney were highly correlated, reflecting numerous links between metabolism and inflammation 50 as well as the inclusion of IL-6 and CRP in both systems, and the contributions of both to kidney aging 51,52 .…”
Section: Discussionmentioning
confidence: 99%